Cloning and Characterization of a Flavonol Synthase Gene from Scutellaria baicalensis - Yeon Bok Kim; KwangSoo Kim; YeJi Kim; Pham Anh Tuan; Haeng Hoon Kim; Jin Woong Cho; Sang Un Park (The Scientific World Journal)
Flavonols are the most abundant of all the flavonoids and play pivotal roles in a variety of plants. We isolated a cDNA clone encoding flavonol synthase from Scutellaria baicalensis (SbFLS). The SbFLS cDNA is 1011 bp long, encodes 336 amino acid residues, and belongs to a family of 2-oxoglutarate-dependent dioxygenases. The overall structure of SbFLS is very similar to that of Arabidopsis thaliana anthocyanidin synthase (AtANS), with a β jelly-roll fold surrounded by tens of short and long α-helices. SbFLS was constitutively expressed in the roots, stems, leaves, and flowers, with particularly high expression in the roots and flowers. SbFLS transcript levels in the roots were 376-, 70-, and 2.5-fold higher than in the leaves, stems, and flowers. The myricetin content was significantly higher than that of kaempferol and quercetin. Therefore, we suggest that SbFLS mediates flavonol formation in the different organs of S. baicalensis. Our study may contribute to the knowledge of the role of FLS in S. baicalensis.